Applying energy efficiency strategies to university buildings using Design Builder program "Case study of the Faculty of Commerce building at Sohag University as a case study" تطبيق إستراتيجيا ت رفع كفاءة الطاقة على إستهلاكها في المباني الجامعية بإستخدام برنامجDesign Builder " دراسة حالة مبنى كلية التجارة بجامعة سوهاج كحالة دراسة" - Heba Talah Anwar khelef; Ahmed A Farghaly; Mohamed H ElHafnawy (JES: Journal of Engineering Sciences)
University buildings consume a large percentage of energy rates in buildings in general due to their occupants, their activities and their occupancy pattern, as the higher education sector constitutes a small but important part of the existing global buildings sector, which is 20% of the non-residential horizontal area. Universities can be considered “small cities” due to their size, number of occupants, and various complex activities. Therefore, huge energy savings can be achieved when improving and raising the efficiency of energy consumption in this sector. Therefore, the research focuses on evaluating the energy efficiency of university educational buildings, the standards followed to reduce energy consumption in the educational building and identifying the most important strategies that must be followed to adapt university buildings using the Design Builder program, as many universities around the world have moved to reduce energy consumption in buildings and university campuses to be a nucleus for spreading awareness in the wider community about the importance of energy efficiency due to the huge potential for reducing energy in this sector. The research concluded with a set of results, the most important of which are: The use of double walls is an effective means of increasing the thermal conductivity of the wall; The thermal conductivity of a material increases with the thickness of that material, and the total thermal conductivity of a multi-layer material is the sum of the thermal conductivity of all the layers inside it. The effect of different alternatives on the energy consumption of the roof varies, but the most effective alternative is to make a canopy of wood with a green roof underneath it. Sunbreakers also have a greater effect when used on the windows of the southern facade. الملخص تستهلك المباني الجامعية نسبة كبيرة من معدلات الطاقة في المباني بشكل عام بسبب شاغليها وأنشطتهم ونمط إشغالها، حيث يشكل قطاع التعليم العالي جزءاً صغيراً ولكن هاماً من قطاع المباني العالمية القائمة والمتمثل في 20 % من المساحة الأفقية غير السكنية، فيمكن إعتبار الجامعات ”مدن صغيرة” نظراً لحجمها، وعدد شاغليها، والأنشطة المعقدة المختلفة بها، وبالتالي يمكن تحقيق وفورات ضخمة في الطاقة عند تحسين ورفع كفاءة إستهلاك الطاقة في هذا القطاع، لذا يركز البحث على تقييم كفاءة الطاقة في المباني التعليمية الجامعية، والمعايير المتبعة لخفض إستهلاك الطاقة في المبنى التعليمي وتحديد أهم الإستراتيجيات التي يجب إتباعها لتكيف المباني الجامعية وذلك بإستخدام برنامحDesign Builder، حيث إتجهت العديد من الجامعات على مستوى العالم إلى خفض إستهلاك الطاقة في المباني والحرم الجامعي لتكون نواه لنشر الوعي في المجتمع الأوسع بأهمية كفاءة الطاقة نظراً للإمكانيات الضخمة لتخفيض الطاقة في هذا القطاع. وقد خلص البحث إلى مجموعة من النتائج أهمها: أن إستخدام الحوائط المزدوجة من الوسائل الفعالة لزيادة الموصلية الحرارية للحائط؛ حيث تزداد الموصلية الحرارية للمادة بزيادة سمك هذه المادة، كما أن الموصلية الحرارية الكلية لمادة متعددة الطبقات هي مجموع الموصلية الحرارية لكل الطبقات الداخلة بها، ويتفاوت تأثير البدائل المختلفة على إستهلاك الطاقة بالسقف، إلا أن أكثر البدائل فاعلية كان عمل مظلة من الخشب وأسفلها سقف أخضر، كما تؤثر كاسرات الشمس بشكل أكبر عند إستخدامها على نوافذ الواجهة الجنوبية.